Correlation of Serum Vitamin D Levels with Physical Performance on the Employees of Dr. Mohammad Hoesin Hospital Palembang - Wicaksana, Satria Putra; Lubis, Hendy Rachmat Primana; Ziske, Mariska (Indonesian Research Journal on Education, 2025)
Vitamin D deficiency is prevalent among women with limited sun exposure due to cultural dress codes such as the hijab. This study investigates the correlation between vitamin D status and physical performance among hijab-wearing female hospital employees. A cross-sectional study was conducted among 50 hijab-wearing female employees at a private hospital. Serum 25(OH)D levels were measured, and physical performance was assessed using standardized walk and strength tests. Muscle mass was assessed using Bioelectrical Impedance Analysis (BIA). Multivariate regression analyses adjusted for confounders including sunscreen use, skin pigmentation, and physical activity levels. Although 74% of participants were vitamin D deficient (<20 ng/mL), there was no significant correlation between serum vitamin D levels and physical performance (p > 0.05). Unexpectedly, a weak negative correlation was observed between vitamin D levels and muscle mass. Despite high deficiency rates, physical performance remained unaffected, suggesting possible physiological resilience or unmeasured confounding factors. Routine screening and sun exposure education are recommended for this at-risk group. Further longitudinal studies with objective strength measures are warranted.